Thermal Effect on Co-product Tar Produced with Syngas Through Co-gasification of Coconut Shell and Charcoal - Monir, Minhaj Uddin; Khatun, Fatema; Ramzilah, U. R.; Azrina, Abd Aziz (IOP Publishing, 2020)
Lignocellulosic biomass generated syngas is one of the most promising alternative bioenergy for the fulfillment of future energy demand. However, the presence of tar in syngas may hindrance the direct uses as transportation and electricity generation purposes. Moreover, tar elimination from syngas is one of the major challenges that can cause fouling in pipes and engines. Thus, this study investigates the decomposition of tar compounds by thermal treatment at the temperature of 700 °C, 800 °C, 900 °C and 1000 °C under a digital Muffle Furnace. The raw tar samples (before and after thermal treatment) were investigated by fouriertransform infrared spectroscopy analysis and morphological changes were observed using a scanning electron microscope analysis. From this study, it was found that tar reduction efficiency was significantly affected by thermal treatment and increased from 81.87% to 97.25% at the required temperature from 700 °C to 1000 °C, respectively. Moreover, the roughness of tar increased significantly with increasing the temperature. The phenolic compounds were eliminated from raw tar due to thermal treatment up to 1000 °C. Therefore, this tar-free syngas can be used as clean and sustainable bioenergy for the future energy crisis.